Percepções dos usuários de crack sobre suas relações familiares - Barros, Naiara Alves de [UNIFESP] (2015)
Drug use is a matter of public health, and the use of crack generates individual, family and social consequences, now getting worrying dimensions to the State and society in general. However, few national studies on family relationships of crack users although it is known that the family can be both a protective factor as a risk in relation to the abuse of alcohol or other drugs. This study aimed to understand the crack users perception of their family relationships. And the specific objectives were to understand the dynamics and family composition in childhood and adolescence of crack users, analyze drug use history, identify the access to health and social care services in the city of Santos / SP; and see how the public policies of health and social care are responding to the needs of crack users and their families. The method used was qualitative and the data were analyzed through content analysis. We interviewed 29 crack users of both sexes and aged eighteen years through semistructured interviews. The analysis categories were: family relationships and the fragility of bonds; crack and other drugs in the family context; family support network and access to health and social care services. Various problems faced by households related to drug use was reported, with the support of this was reported by users as an important form of motivation to control the use of this drug. The perception of crack users on its relations with the family of origin reveals the presence of several factors associated with increased vulnerability to drug use. The result of this study can help implement new forms of prevention and intervention with crack users, strengthening for public policies to take effect according to the issues presented by crack users and their families.